School Feeding and Learning Achievement: Evidence from India's Midday Meal Program - Tanika Chakraborty; Rajshri Jayaraman (Center for Economic Studies and ifo Institute (CESifo), 2016)
We study the effect of the world's largest school feeding program on children's learning outcomes. Staggered implementation across different states of a 2001 Indian Supreme Court Directive mandating the introduction of free school lunches in public primary schools generates plausibly exogenous variation in program exposure across different birth cohorts. We exploit this to estimate the effect of program exposure on math and reading test scores of primary school-aged children. We find that midday meals have a dramatic positive effect on learning achievement: children with up to 5 years of primary school exposure improve their test scores by approximately 10-20%. We further investigate various channels that may account for this improvement including enrollment and nutrition-learning effects, heterogeneous responses by socio-economic status, complementary schooling inputs, and intra-household redistribution.
Keywords: I21; I25; O12; 330; school feeding; learning; midday meal; primary school education